Tracing Success of Graduates: A Case Study of Koteshwor Multiple Campus - Pokharel, Suman; Gartaula, Sudeep (KMC Research Journal, 2025)
Tracer studies provide timely, vital information regarding graduate outcomes.This article examines the post-graduation experiences of Koteshwor Multiple Campus alumni from 2020–2022. It looks at how students employ the skills they acquired in their careers, how they enter the workforce, and how they continue to interact with the institution. It seeks to monitor recent graduates and pinpoint the elements influencing their professional decisions. The results, which offer insights to improve academic programs and industrial ties, are critical to KMC’s institutional growth. By encouraging industrial relationships and entrepreneurship, the report also enhances career counseling and KMC’s job placement cell. Finally, this analysis backs mentoring and curriculum modifications to better prepare graduates for the workforce.